Exprerience and Impact of Parenting, Culture on Infant Frowth and Develompment: A Phenomenological Study - Theresia Anita; Tezi Kharina Aprezia; Lezi Mayang Sari (GLOBAL HEALTH SCIENCE GROUP, 2025)
The development of every child in the early stages of life is highly dependent on parents, especially mothers, who will help with all their needs. The purpose of this study is to determine the experience and impact of parenting and environmental patterns on infant growth and development. Method: This study uses a qualitative method with a descriptive phenomenological approach. This study involved 8 participants and with a purposive sampling technique according to the inclusion criteria. Data was collected through interviews and data was analyzed using thematic analysis. Results: Based on the results of the interview analysis conducted, several themes were obtained related to the research objectives, namely: 1) Infant growth and development, 2) Parenting. 3) Culture. 4) The impact of parenting and culture on growth and development. Conclusion: 8 informants have children of different ages. There is no delay in child growth and development, the type of parenting in this study is democratic and authoritative. There are positive and negative impacts of parenting and culture on growth and development.